1996
DOI: 10.1002/ana.410390409
|View full text |Cite
|
Sign up to set email alerts
|

Hypersomnia following paramedian thalamic stroke: A report of 12 patients

Abstract: Paramedian thalamic stroke (PTS) is a cause of organic hypersomnia, which in the absence of systematic sleep-wake studies has been attributed to disruption of ascending activating impulses and considered a "dearoused" state. However, an increasing mount of data suggests a role of the thalamus in sleep regulation and raises the possibility that a sleep disturbance contributes to hypersomnia in PTS. We evaluated 12 patients with magnetic resonance imaging-proven isolated PTS and hypersomnia with 10 to >20 hours … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
128
3
7

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(145 citation statements)
references
References 22 publications
7
128
3
7
Order By: Relevance
“…Bassetti et al (1996), reported in 12 patients showed nocturnal polysomnographic findings paralleled the severity of hypersomnia [128]. Hypersomnia following PTS is accompanied by deficient arousal during the day and insufficient spindling and slow wave production at night, The center of the ischemic lesion was the inferior region of dorsomedial nucleus(DM) and the medial anterior part of the CM(centromedian neucles), confirming the autopsy study of Castaine et al [131].…”
Section: Sleep the Distribution Of Spindles Recovery After Strokesupporting
confidence: 60%
“…Bassetti et al (1996), reported in 12 patients showed nocturnal polysomnographic findings paralleled the severity of hypersomnia [128]. Hypersomnia following PTS is accompanied by deficient arousal during the day and insufficient spindling and slow wave production at night, The center of the ischemic lesion was the inferior region of dorsomedial nucleus(DM) and the medial anterior part of the CM(centromedian neucles), confirming the autopsy study of Castaine et al [131].…”
Section: Sleep the Distribution Of Spindles Recovery After Strokesupporting
confidence: 60%
“…[1][2][3][4] Patients typically also exhibit neurological symptoms such as vertical gaze palsy and other oculomotor deficits, Horner's syndrome, dysarthria, gait ataxia, and mild sensorimotor deficits. 3,[5][6][7][8][9][10] With the improvement of consciousness, neuropsychological problems such as executive, learning, and memory deficits become more evident.…”
mentioning
confidence: 99%
“…Paramedian talamik inme sonrası gelişen talamik hipersomninin patogenezinde ise, beyin sapı retiküler formasyondan talamusa uzanan noradrenerjik ve dopaminerjik aktive edici uyarıların oluşmaması vardır (4,5,7,8,9). Bassetti ve ark.…”
Section: Olguunclassified
“…Talamusun vasküler sendromları üzerine yapılan çalışmalarda, özellikle paramedian arter infarktlarında uyanıklığın belirgin bir şekilde azaldığı belirtilmiştir (2). Hipersomni denilen bu durumun tedavisinde, aralarında levodopa'nın da bulunduğu bazı ilaçların faydalı olduğu bildirilmiştir (3)(4)(5). Burada, bilateral paramedian talamik infarkt sonrası hipersomni gelişen bir olgu ve uygulanan levodopa tedavisine verdiği olumlu yanıt sunulmaktadır.…”
Section: Introductionunclassified